1984
DOI: 10.1093/oxfordjournals.eurheartj.a061645
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene D4-induced vasoconstriction of coronary arteries in anaesthetized dogs

Abstract: We examined in pentobarbital-anaesthetized dogs, the effects of intracoronary leukotriene D4 (LTD4) on large vessel (circumflex artery) flow and diameter and on calculations of late diastolic and total coronary resistance. Heart rate, systolic and end-diastolic ventricular pressures and the dP/dt were the haemodynamic variables studied. The peripheral ECG was obtained in lead II. LTD4 (0.1-10 micrograms kg-1) reduced coronary diameter up to 12 +/- 3% (mean +/- s.e.m.). Coronary flow decreased in dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Subsequent to the early investigations , which reported that partially purified SRS markedly reduced coronary blood flow, a number of other investigators have explored the cardiovascular effects of the cys-LTs in a variety of different animal models. The early studies have shown that the cys-LTs are potent vasoconstrictors of the coronary vasculature in both isolated perfused hearts (Woodman and Dusting, 1982; and in a number of species in vivo (Michelassi et al, 1982;Panzenbeck and Kaley, 1983;Fiedler et al, 1984Leffler et al, 1984;Kopia et al, 1987;Michelassi et al, 1987) including human (Marone et al, 1988). In sheep and pigs, cys-LTs induced not only coronary vasoconstriction but also ischemia and impaired left ventriclar function (Michelassi et al, 1982;Ezra et al, 1983;Fiedler et al, 1985).…”
Section: Vascular Smooth Muscle Contractionmentioning
confidence: 99%
“…Subsequent to the early investigations , which reported that partially purified SRS markedly reduced coronary blood flow, a number of other investigators have explored the cardiovascular effects of the cys-LTs in a variety of different animal models. The early studies have shown that the cys-LTs are potent vasoconstrictors of the coronary vasculature in both isolated perfused hearts (Woodman and Dusting, 1982; and in a number of species in vivo (Michelassi et al, 1982;Panzenbeck and Kaley, 1983;Fiedler et al, 1984Leffler et al, 1984;Kopia et al, 1987;Michelassi et al, 1987) including human (Marone et al, 1988). In sheep and pigs, cys-LTs induced not only coronary vasoconstriction but also ischemia and impaired left ventriclar function (Michelassi et al, 1982;Ezra et al, 1983;Fiedler et al, 1985).…”
Section: Vascular Smooth Muscle Contractionmentioning
confidence: 99%
“…Since indomethacin cannot block these negative inotropic actions of both reagents, the cardiodepressant PAF effects are not mediated by cyclooxygenase products, e.g., TxA2. A negative inotropic effect has also been shown for leukotrienes (17,18,24,38,39), and was related to an inhibition of transsarcolemmal calcium influx (39).…”
Section: Discussionmentioning
confidence: 88%
“…Besides others (16), we have recently shown (17)(18)(19) that LTD4 can increase coronary arterial tone and resistance and diminishes the external diameter of canine epicardial coronary arteries (17).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Some recent observations have suggested that calcium ion fluxes might be important in mediating the effects of leukotrienes in non-vascular (Findlay et al, 1982;Weichmann et al, 1983;Kohrogi et al, 1985) and in coronary vascular smooth muscle in vitro (Roth & Lefer, 1983;Fiedler et al, 1984). The capacity of (b) Figure 4.…”
Section: Discussionmentioning
confidence: 96%